Quasi-solid sodium metal battery with high stable interface and electrolyte preparation method thereof

CN122889823APending Publication Date: 2026-10-09SHANGHAI WEINA NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611246965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

第一,现有凝胶聚合物电解质的化学调控手段(如添加剂、溶剂优化)与机械增强手段(如交联、填料复合)通常相互独立,缺乏分子尺度上的协同设计,难以在同一体系中同时实现界面化学惰性的提升与力学适应性的增强

Benefits of technology

本发明通过“溶剂-聚合物齿轮啮合效应”实现了界面化学稳定性与机械稳定性的同步增强,克服了现有技术中化学调控与机械增强相互独立、难以协同的缺陷,为抑制准固态钠金属电池的化学-机械耦合失效提供了系统性的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889823A_ABST
    Figure CN122889823A_ABST
Patent Text Reader

Abstract

The application discloses a quasi-solid sodium metal battery with a high-stable interface and a preparation method of an electrolyte thereof, and belongs to the technical field of electrochemical energy storage. The battery comprises a positive electrode, a sodium metal negative electrode and a gel polymer electrolyte interposed therebetween. The electrolyte is formed by in-situ polymerization of a polymer matrix containing electronegative functional groups, a sodium salt, a mixed organic solvent containing electropositive hydrogen atoms and a cross-linking agent. The electronegative functional groups and the electropositive hydrogen atoms are combined through electrostatic interaction and van der Waals force, a dynamic non-covalent cross-linking network of a "solvent-polymer gear meshing effect" is formed in the electrolyte, and a composite interface structure which is chemically stable and mechanically enhanced is simultaneously constructed at the positive electrode / electrolyte interface. The application can effectively inhibit the chemical-mechanical coupling failure of the quasi-solid sodium metal battery, and excellent cycle stability is exhibited under high positive electrode load and low temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a quasi-solid-state sodium metal battery with a highly stable interface and a method for preparing its electrolyte. Background Technology

[0002] Sodium-ion batteries, due to the abundance and low cost of sodium resources, have shown broad application prospects in large-scale energy storage. Among them, sodium metal batteries, which use sodium metal as the negative electrode, benefit from the high theoretical specific capacity of sodium metal (approximately 1165 mAh g⁻¹). -1 With its low redox potential (approximately -2.71 V vs. SHE), sodium metal batteries are considered strong candidates for next-generation high-energy-density energy storage systems. Quasi-solid-state sodium metal batteries employing gel polymer electrolytes combine the high ionic conductivity of liquid batteries with the high safety of solid-state batteries, and have attracted widespread attention in recent years.

[0003] However, the commercialization of quasi-solid-state sodium metal batteries faces severe challenges in interface stability, mainly manifested in the coupling of the following two failure modes: Chemical failure: The organic solvent components in gel polymer electrolytes are prone to oxidative decomposition on the surface of high-voltage / high-activity cathodes (such as layered oxide cathodes). Simultaneously, transition metal ions (such as Mn, Co, Ni, etc.) in the cathode active material dissolve under the chemical erosion of the electrolyte, leading to cathode structural degradation and capacity decay. Furthermore, the high reactivity of the sodium metal anode causes continuous side reactions between it and the electrolyte, generating a thick and non-uniform solid electrolyte interfacial film, further exacerbating the increase in interfacial impedance.

[0004] Mechanical failure: Sodium metal anodes undergo significant volume changes during deposition / stripping (without host characteristics), while cathode materials also experience lattice expansion and contraction during charge-discharge cycles. These periodic volume changes generate heterogeneous stress fields at the electrode / electrolyte interface. When the mechanical properties of the gel polymer electrolyte are insufficient to buffer these stresses, it will lead to interfacial contact failure, interfacial delamination, or even cathode particle breakage.

[0005] The aforementioned chemical and mechanical failures are coupled and mutually exacerbated in actual operation: the accumulation of interfacial by-reaction products further deteriorates the interfacial mechanical contact, while interfacial peeling exposes fresh surfaces and accelerates by-reactions, forming a "chemical-mechanical coupling failure" that severely restricts the long-term cycle life of the battery, especially at high positive electrode loading (≥5 mg cm⁻¹). -2 Under harsh conditions such as low temperature.

[0006] To address the aforementioned issues, several improvement schemes have been developed in the existing technology. For example, introducing halobenzene additives into the gel polymer electrolyte matrix helps form a halide-rich electrode-electrolyte interface film, thus alleviating solid-solid interface contact problems; or using a high-pressure all-ether gel electrolyte system can improve the electrolyte's antioxidant capacity; some studies have also explored the introduction of fluorine-containing groups into the polymer backbone to improve interfacial stability. Furthermore, researchers have proposed an anion trapping-interface coupling strategy, constructing a composite gel electrolyte by introducing highly cross-linked boron nitride nanosheets onto a glass fiber matrix to enhance mechanical properties and interfacial stability.

[0007] However, the aforementioned existing technical solutions mostly focus on improving only one aspect—either emphasizing chemical stability (such as film formation with additives and modification with fluorinated groups) or mechanical properties (such as introducing reinforcing fillers and constructing cross-linked networks), making it difficult to systematically solve the coupling problem of chemical and mechanical failures simultaneously. Specifically: First, existing chemical regulation methods (such as additives and solvent optimization) and mechanical enhancement methods (such as crosslinking and filler composites) for gel polymer electrolytes are usually independent of each other and lack synergistic design at the molecular scale, making it difficult to simultaneously improve interfacial chemical inertness and enhance mechanical adaptability in the same system.

[0008] Second, the interfacial bonding between the gel electrolyte prepared by existing in-situ polymerization and the electrode is mostly physical contact, lacking strong interactions at the molecular level, and is prone to interfacial delamination during repeated volume changes of the electrode.

[0009] Third, existing technologies for regulating the cathode / electrolyte interface (CEI) mostly rely on external additives, lacking strategies to drive spontaneous optimization of interface chemistry through intermolecular interactions within the electrolyte bulk.

[0010] Therefore, developing a quasi-solid-state sodium metal battery and its electrolyte preparation method that can simultaneously enhance interfacial chemical and mechanical stability and suppress chemical-mechanical coupling failure at the molecular level is of great technical significance and application value. Summary of the Invention

[0011] In order to overcome the above-mentioned defects of the prior art, the present invention provides a quasi-solid-state sodium metal battery with a highly stable interface and a method for preparing the electrolyte thereto, so as to solve the problems existing in the background art.

[0012] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A quasi-solid-state sodium metal battery with a highly stable interface includes a positive electrode, a sodium metal negative electrode, and a gel polymer electrolyte between the positive electrode and the sodium metal negative electrode. The gel polymer electrolyte is formed by in-situ polymerization of a polymer matrix, a sodium salt, a mixed organic solvent and a crosslinking agent; The polymer matrix contains electronegative functional groups, and the mixed organic solvent contains electropositive hydrogen atoms; The electronegative functional groups and the electropositive hydrogen atoms are bonded through electrostatic interaction and van der Waals force to form a dynamic non-covalent crosslinked network inside the gel polymer electrolyte; The dynamic non-covalent crosslinked network is used to synchronously construct a chemically stable and mechanically reinforced composite interface structure at the interface between the positive electrode and the gel polymer electrolyte.

[0013] In the above technical solution, the electronegative functional group is a fluorine-containing functional group, preferably trifluoromethyl (-CF3); the polymer matrix is a fluorine-containing acrylate polymer or copolymer, preferably at least one of poly(2,2,2-trifluoroethyl acrylate) and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0014] In the above technical solution, the mixed organic solvent comprises a carbonate solvent and a phosphate ester solvent, preferably a mixture of propylene carbonate and triethyl phosphate, wherein the volume ratio of propylene carbonate to triethyl phosphate is 10:1 to 1:10.

[0015] In the above technical solution, the sodium salt is a sodium salt whose anions are prone to reductive decomposition at the positive electrode interface, preferably at least one of sodium bis(fluorosulfonyl)imide, sodium perchlorate and sodium hexafluorophosphate; the concentration of the sodium salt in the mixed organic solvent is 0.5 M to 5 M.

[0016] In the above technical solution, the crosslinking agent is a compound containing at least two polymerizable double bonds, preferably at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and trimethylolpropane triacrylate.

[0017] In the above technical solution, the positive electrode is a layered oxide positive electrode, and the general formula of the active material thereof is NaNi X M (1-X) O2, wherein M is one or more of Mn, Fe, Co, Ti, Mg, Al, Cu, Zn and Zr, and 0<x<1; the areal loading of the active material of the positive electrode is greater than or equal to 5 mg cm -2 .

[0018] A method for preparing the above quasi-solid-state sodium metal battery, comprising the following steps: S1. Preparation of electrolyte precursor solution: Under an inert atmosphere, sodium salt is dissolved in a mixed organic solvent composed of carbonate solvent and phosphate ester solvent, and stirred thoroughly to obtain a homogeneous sodium salt solution; then, monomers containing electronegative functional groups, crosslinking agents and thermal initiators are added to the sodium salt solution in sequence, and the mixture is stirred continuously to obtain a clear and homogeneous gel polymer electrolyte precursor solution. S2. Processing of positive electrode sheet: providing a pre-dried positive electrode sheet, the positive electrode sheet comprising a current collector and a layer of positive active material coated thereon; S3. Introduction and wetting of precursor solution: The precursor solution obtained in step S1 is introduced into the positive electrode sheet in step S2 by drop coating, immersion or vacuum-assisted wetting, so that the solution fully wets the surface and internal pores of the positive electrode active material layer. S4. In-situ polymerization to form a composite positive electrode: The impregnated positive electrode sheet is placed in an inert atmosphere and heated at a temperature of 50°C to 90°C to initiate a thermal polymerization reaction between the monomer and the crosslinking agent. The reaction time is 2 to 24 hours, thereby forming a gel polymer electrolyte layer that is tightly bonded to the electrode in situ inside and on the surface of the positive electrode sheet, thus obtaining an integrated composite positive electrode. S5. Battery assembly: Under an inert atmosphere, the integrated composite positive electrode, sodium metal negative electrode, and optionally the separator obtained in step S4 are assembled, and an auxiliary electrolyte is added or the battery is directly sealed to obtain the quasi-solid-state sodium metal battery.

[0019] In the above method, the monomer in step S1 is a fluorinated acrylate monomer, preferably 2,2,2-trifluoroethyl acrylate; the thermal initiator is an azo or peroxide initiator, preferably azobisisobutyronitrile.

[0020] In the above method, the reaction temperature of the in-situ polymerization in step S4 is 50°C to 90°C, and the reaction time is 2 hours to 24 hours.

[0021] The application of a gel polymer electrolyte in the preparation of a quasi-solid-state sodium metal battery, wherein the gel polymer electrolyte is the gel polymer electrolyte used in the aforementioned quasi-solid-state sodium metal battery; the application includes a temperature range of -20°C to 60°C and an areal loading of positive electrode active material greater than or equal to 5 mg cm⁻¹. -2 Under certain conditions, the quasi-solid-state sodium metal battery can undergo stable charge-discharge cycles.

[0022] The technical effects and advantages of this invention are as follows: This invention achieves simultaneous enhancement of interfacial chemical stability and mechanical stability through the "solvent-polymer gear meshing effect," overcoming the shortcomings of existing technologies where chemical regulation and mechanical enhancement are independent and difficult to coordinate, and providing a systematic solution for suppressing the chemical-mechanical coupling failure of quasi-solid-state sodium metal batteries.

[0023] This invention utilizes the electrostatic interaction between the electronegative functional groups of the polymer matrix and the electronegative hydrogen atoms of the solvent molecule to in situ regulate the Na+ content. + The solvation structure drives anions into the solvation sheath, thereby spontaneously forming an anion-derived, highly stable CEI film on the positive electrode surface without the need for external film-forming additives, simplifying the electrolyte formulation.

[0024] This invention constructs a dynamic non-covalent cross-linked network within the gel electrolyte through the "gear meshing effect," enabling the gel electrolyte to maintain high ionic conductivity while possessing excellent mechanical properties (viscoelasticity, strength, interfacial adhesion, and resilience). This effectively buffers the stress caused by changes in electrode volume and prevents interfacial peeling and particle breakage.

[0025] This invention uses in-situ polymerization to prepare an integrated composite cathode, which enables the gel polymer electrolyte and the cathode active material to form a tight molecular-level bond, resulting in low interfacial impedance and high interfacial stability.

[0026] The quasi-solid-state sodium metal battery of this invention features high positive electrode loading (≥9 mg / cm³). -2 It maintains good cycling stability even under low temperature conditions (such as -15°C), making it suitable for applications with a wide temperature range and high energy density. Attached Figure Description

[0027] Figure 1 This is a flowchart of the preparation method of the present invention.

[0028] Figure 2 This is a schematic diagram of the test results in Embodiment 3 of the present invention.

[0029] Figure 3 This is a schematic diagram of the test results in Embodiment 4 of the present invention. Detailed Implementation

[0030] The technical solution of the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. These embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.

[0031] Example 1: This example provides a quasi-solid-state sodium metal battery based on poly(2,2,2-trifluoroethyl acrylate) gel polymer electrolyte and its preparation method.

[0032] 1. Preparation of gel polymer electrolyte precursor solution In a glove box filled with argon (both H2O and O2 concentrations are below 0.1 ppm), proceed as follows: (1) Mix propylene carbonate (PC) and triethyl phosphate (TEP) at a volume ratio of 1:1, add 4 Å molecular sieve and dry for more than 24 hours to obtain a mixed organic solvent.

[0033] (2) Accurately weigh 2.10 g (approximately 7.4 mmol) of sodium difluorosulfonamide (NaFSI, purity ≥99.5%) that has been vacuum dried at 120°C for 24 hours, and add it to 5.0 mL of the above mixed organic solvent. Stir magnetically at 25°C for 18 hours to completely dissolve the NaFSI, yielding a clear and transparent solution of approximately 1.0 mol / L. -1 NaFSI solution.

[0034] (3) Add the following to the NaFSI solution in sequence: Monomer: 0.75g 2,2,2-trifluoroethyl acrylate (TFEA, purity >99%, purified by vacuum distillation); Crosslinking agent: 30mg polyethylene glycol diacrylate (PEGDA, number average molecular weight Mn≈400); Thermal initiator: 7.5 mg azobisisobutyronitrile (AIBN, recrystallized from ethanol).

[0035] (4) Continue to stir the above mixture in a glove box for 24 hours to obtain a completely homogeneous and clear gel polymer electrolyte precursor solution (referred to as "solution A").

[0036] The formulation composition of the gel polymer electrolyte precursor solution described in Example 1 is shown in Table 1.

[0037] Table 1. Formulation of gel polymer electrolyte precursor solution in Example 1.

[0038]

[0039] 2. Preparation of integrated composite cathode (1) Preparation of the positive electrode: using O3-type layered oxide NaNi 0.4 Mn 0.4 Ti 0.2 O2, the positive electrode active material, is mixed with conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) binder at a mass ratio of 92:4:4 to form a slurry, which is then uniformly coated onto an aluminum foil current collector. After coating, it is vacuum dried at 120°C for 12 hours, rolled, and then punched into discs with a diameter of 12 mm. The areal density of the active material is approximately 5.5 mg / cm³. -2 The electrodes were dried again in a vacuum oven at 120°C for 12 hours before assembly and then transferred to a glove box.

[0040] (2) Introduction and wetting of the precursor solution: Place one of the above-mentioned positive electrode sheets in a 20 mL glass sample bottle, and use a pipette to transfer 150 µL of "Solution A" and evenly drop it onto the surface of the electrode sheet. After sealing the sample bottle, remove it from the glove box, connect it to the vacuum pump, and maintain it under a negative pressure of -0.095 MPa for 5 minutes to allow the solution to fully penetrate into the internal pores of the electrode, resulting in a uniform gloss on the surface. After releasing the vacuum, quickly move the sample bottle back to the argon-filled glove box.

[0041] (3) In-situ thermal polymerization: Place the sample vial on a 70 °C constant temperature heating table in a glove box and heat for 12 hours for polymerization. After polymerization, a transparent, elastic gel film is formed on the surface of the positive electrode sheet and is tightly bonded to the electrode, thus obtaining an integrated composite positive electrode (denoted as "composite positive electrode B1").

[0042] 3. Assembly of Quasi-Solid-State Sodium Metal Batteries Assemble the CR2032 button cells in the following order within an argon atmosphere glove box: Using composite cathode B1 as the positive electrode; A 16mm diameter glass fiber diaphragm is placed over the positive electrode; Add 30µL of liquid electrolyte (1M NaFSIinPC / TEP, volume ratio 1:1) as an interfacial wetting supplement; Place a sodium metal sheet with a diameter of 15 mm and a thickness of 0.5 mm as the negative electrode; Using CR2032 battery casing, gaskets, and springs, a quasi-solid-state sodium metal battery (denoted as "Battery Cell-B1") was prepared by sealing it with a pressure of 800 kgf on a sealing machine.

[0043] 4. Electrochemical performance testing Place the Cell-B1 battery in a 25°C constant temperature chamber, first at 0.05°C (1C=120mAg). -1 Two cycles of formation were performed. Subsequently, constant current charge-discharge tests were conducted at 0.5C within a voltage range of 2.0-4.0V.

[0044] Test results show that the battery's initial discharge specific capacity is 118.3 mAhg. -1 After 300 cycles, the discharge specific capacity was 105.7 mAh g. -1 The capacity retention rate was 89.4%, and the average coulombic efficiency was higher than 99.8%.

[0045] The main electrochemical performance parameters of the battery described in Example 1 are shown in Table 2. Table 2 Summary of electrochemical performance of the battery in Example 1:

[0046]

[0047] Comparative Example 1: This comparative example provides a control battery using a non-fluorinated polymer, with all other conditions being the same as in Example 1.

[0048] The precursor solution was prepared in the same manner as in Example 1, except that ethyl acrylate (EA) was used instead of 2,2,2-trifluoroethyl acrylate (TFEA) as the monomer, i.e., a polymer matrix without electronegative trifluoromethyl functional groups was used. The remaining components (NaFSI, PC / TEP mixed solvent, PEGDA crosslinking agent, AIBN initiator) and their amounts and preparation conditions were the same as in Example 1.

[0049] The preparation, battery assembly, and testing conditions for the composite cathode were the same as in Example 1.

[0050] Test results show that the initial discharge specific capacity of the control battery is 115.6 mAhg. -1 After 300 cycles, the capacity retention rate was only 65.2%, significantly lower than the 89.4% in Example 1. This indicates that the polymer matrix without electronegative functional groups cannot form a "gear meshing effect," and the interfacial stability is significantly reduced.

[0051] Table 3 shows a comparison of the cyclic performance of Example 1 and Comparative Example 1.

[0052] Table 3 Comparison of cycle performance between Example 1 and Comparative Example 1:

[0053]

[0054] Example 2: This example is used to verify the performance of the present invention under high positive electrode load and low temperature conditions.

[0055] 1. Preparation of high-load composite cathode Using the same material formulation and preparation process as in Example 1, the difference lies in adjusting the coating process to achieve an active substance areal density of 9.5 mg / cm³. -2 High-load positive electrode sheet (12mm in diameter).

[0056] The precursor solution was prepared in the same manner as "Solution A" in Example 1.

[0057] Impregnation and polymerization: The high-load positive electrode sheet was placed in a sealable Teflon mold, and 250 µL of "solution A" was injected until the electrode sheet was completely submerged. The mold was placed in a vacuum chamber, evacuated to -0.1 MPa, and maintained for 15 minutes. Subsequently, under the condition of maintaining negative pressure, the entire mold was moved into a 70°C oven, and the polymerization reaction was carried out for 16 hours. After cooling, it was removed to obtain a high-load composite positive electrode with a gel skeleton support (denoted as "composite positive electrode B2").

[0058] 2. Battery assembly and room temperature testing The battery assembly method is the same as in Example 1, using composite positive electrode B2 to obtain battery Cell-B2-H.

[0059] At 25°C, with a concentration of 0.2C (1C = 120mAg) -1 Perform charge and discharge tests.

[0060] Test results show that the initial discharge specific capacity is 122.5 mAh g. -1 (Based on the mass of active material), the discharge specific capacity after 100 cycles is 108.7 mAh g. -1 The capacity retention rate was 88.7%.

[0061] 3. Low-temperature performance test Another cell, Cell-B1-LT, with the same process as in Example 1, was assembled for low-temperature testing.

[0062] The Cell-B1-LT battery was placed in a -15°C cryogenic chamber and left to stand for 4 hours to reach thermal equilibrium. Charge and discharge tests were then conducted at a rate of 0.1C within a voltage range of 2.0-4.0V and at -15°C.

[0063] Test results show that the battery's initial discharge specific capacity at -15°C is 102.1 mAhg. -1 After 50 cycles at 0.1C, the discharge specific capacity is 95.4 mAh g. -1 The capacity retention rate was 93.5%, the charge and discharge platform was stable, and the increase in polarization voltage was not significant.

[0064] The main electrochemical performance parameters of Example 2 are shown in Table 4.

[0065] Table 4 Summary of Electrochemical Performance of Batteries in Example 2

[0066]

[0067] Example 3: This example provides an implementation scheme using different sodium salts and different solvent ratios.

[0068] The preparation method of the precursor solution is the same as in Example 1, except that: (1) Sodium salt is replaced by sodium perchlorate (NaClO4) at a concentration of 1.0 mol / L. -1 ; (2) The volume ratio of propylene carbonate (PC) to triethyl phosphate (TEP) in the mixed organic solvent is 2:1; (3) The amount of monomer TFEA added accounts for 12% of the total mass of the precursor solution.

[0069] The remaining steps (composite cathode preparation, battery assembly, and testing conditions) are the same as in Example 1.

[0070] The formulation composition of the gel polymer electrolyte precursor solution described in Example 3 is shown in Table 5.

[0071] Table 5. Formulation of Gel Polymer Electrolyte Precursor Solution in Example 3

[0072]

[0073] like Figure 2 The test results show that the quasi-solid-state sodium metal battery assembled under this implementation scheme has a capacity retention rate of 86.5% after 200 cycles at 25°C and 0.5 C rate, which also shows good cycle stability.

[0074] Example 4: This example provides an implementation scheme using different polymer matrices.

[0075] The preparation method of the precursor solution is the same as in Example 1, except that: (1) The polymer monomer adopts the precursor system of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), that is, PVDF-HFP is used as the polymer matrix raw material (instead of in-situ polymerization of TFEA monomer). (2) Dissolve PVDF-HFP in a PC / TEP mixed solvent, add NaFSI, crosslinking agent PEGDA and initiator AIBN, and stir until homogeneous to obtain a precursor solution; (3) The remaining components and proportions are the same as in Example 1.

[0076] The formulation composition of the gel polymer electrolyte precursor solution described in Example 4 is shown in Table 6.

[0077] Table 6. Formulation of Gel Polymer Electrolyte Precursor Solution in Example 4

[0078]

[0079] The preparation, battery assembly, and testing conditions for the composite cathode were the same as in Example 1.

[0080] like Figure 3 Test results show that the quasi-solid-state sodium metal battery assembled under this implementation scheme retains 81.7% of its capacity after 200 cycles at 25°C and 0.5 C rate.

[0081] Summary of performance comparisons of various embodiments The main formulation variables and electrochemical performance of Examples 1-4 and Comparative Example 1 are summarized in Table 7.

[0082] Table 7 Comparison of main formulation variables and performance of each embodiment and comparative example

[0083]

[0084] As shown in Table 7, Examples 1-4, using the electronegative functional group-containing polymer matrix described in this invention, all exhibited better capacity retention than Comparative Example 1 (without -CF3 groups), verifying the general enhancing effect of the "solvent-polymer gear meshing effect" on interfacial stability. Among them, Example 1 maintained 89.4% capacity retention after 300 long cycles, making it the best performing example overall. Example 2 further verified the effectiveness of this invention at high loading (9.5 mg cm⁻¹). -2 The effectiveness under low-temperature (-15°C) conditions was demonstrated, with capacity retention rates reaching 88.7% (100 cycles) and 93.5% (50 cycles), respectively. Examples 3 and 4 show that the technical solution of the present invention is universally applicable under different sodium salt types (NaClO4) and different polymer matrices (PVDF-HFP).

[0085] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A quasi-solid-state sodium metal battery with a highly stable interface, characterized in that, It includes a positive electrode, a sodium metal negative electrode, and a gel polymer electrolyte between the positive electrode and the sodium metal negative electrode; The gel polymer electrolyte is formed by in-situ polymerization of a polymer matrix, sodium salt, mixed organic solvent and crosslinking agent; The polymer matrix contains electronegative functional groups, and the mixed organic solvent contains electronegative hydrogen atoms; The electronegative functional groups and the electronegative hydrogen atoms are bonded together through electrostatic interactions and van der Waals forces, forming a dynamic non-covalent cross-linked network inside the gel polymer electrolyte; The dynamic non-covalent crosslinked network is used to simultaneously construct a chemically stable and mechanically reinforced composite interface structure at the interface between the positive electrode and the gel polymer electrolyte.

2. The quasi-solid-state sodium metal battery with a highly stable interface according to claim 1, characterized in that, The electronegative functional group is a fluorine-containing functional group, preferably trifluoromethyl; the polymer matrix is ​​a fluorine-containing acrylate polymer or copolymer, preferably at least one of poly(2,2,2-trifluoroethyl acrylate) and polyvinylidene fluoride-hexafluoropropylene copolymer.

3. A quasi-solid-state sodium metal battery with a highly stable interface according to claim 1, characterized in that, The mixed organic solvent comprises carbonate solvents and phosphate solvents, preferably a mixture of propylene carbonate and triethyl phosphate, wherein the volume ratio of propylene carbonate to triethyl phosphate is 10:1 to 1:

10.

4. A quasi-solid-state sodium metal battery with a highly stable interface according to claim 1, characterized in that, The sodium salt is a sodium salt whose anion can undergo reduction decomposition at the positive electrode interface, preferably at least one of sodium difluorosulfonamide, sodium perchlorate, and sodium hexafluorophosphate; the concentration of the sodium salt in the mixed organic solvent is 0.5M to 5M.

5. A quasi-solid-state sodium metal battery with a highly stable interface according to claim 1, characterized in that, The crosslinking agent is a compound containing at least two polymerizable double bonds, preferably at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and trimethylolpropane triacrylate.

6. A quasi-solid-state sodium metal battery with a highly stable interface according to claim 1, characterized in that, The positive electrode is a layered oxide positive electrode, and the general formula of the active material thereof is NaNi X M (1-X) O2, wherein M is one or more of Mn, Fe, Co, Ti, Mg, Al, Cu, Zn and Zr, and 0<x<1; the area loading of the active material of the positive electrode is greater than or equal to 5mgcm -2 , preferably greater than or equal to 9mgcm -2 .

7. A method for preparing a quasi-solid-state sodium metal battery as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of electrolyte precursor solution: Under an inert atmosphere, sodium salt is dissolved in a mixed organic solvent composed of carbonate solvent and phosphate ester solvent, and stirred thoroughly to obtain a homogeneous sodium salt solution; then, monomers containing electronegative functional groups, crosslinking agents and thermal initiators are added to the sodium salt solution in sequence, and the mixture is stirred continuously to obtain a clear and homogeneous gel polymer electrolyte precursor solution. S2. Processing of positive electrode sheet: providing a pre-dried positive electrode sheet, the positive electrode sheet comprising a current collector and a layer of positive active material coated thereon; S3. Introduction and wetting of precursor solution: The precursor solution obtained in step S1 is introduced into the positive electrode sheet in step S2 by drop coating, immersion or vacuum-assisted wetting, so that the solution fully wets the surface and internal pores of the positive electrode active material layer. S4. In-situ polymerization to form a composite positive electrode: The impregnated positive electrode sheet is placed in an inert atmosphere and heated at a temperature of 50°C to 90°C to initiate a thermal polymerization reaction between the monomer and the crosslinking agent. The reaction time is 2 to 24 hours, thereby forming a gel polymer electrolyte layer that is tightly bonded to the electrode in situ inside and on the surface of the positive electrode sheet, thus obtaining an integrated composite positive electrode. S5. Battery assembly: Under an inert atmosphere, the integrated composite positive electrode, sodium metal negative electrode, and optionally the separator obtained in step S4 are assembled, and an auxiliary electrolyte is added or the battery is directly sealed to obtain the quasi-solid-state sodium metal battery.

8. The method according to claim 7, characterized in that, The monomer mentioned in step S1 is a fluorinated acrylate monomer, preferably 2,2,2-trifluoroethyl acrylate; the thermal initiator is an azo or peroxide initiator, preferably azobisisobutyronitrile.

9. The method according to claim 7, characterized in that, The reaction temperature for the in-situ polymerization in step S4 is 50°C to 90°C, and the reaction time is 2 hours to 24 hours.

10. The application of a gel polymer electrolyte in the preparation of quasi-solid-state sodium metal batteries, characterized in that, The gel polymer electrolyte is the gel polymer electrolyte in the quasi-solid-state sodium metal battery according to any one of claims 1-6; the application includes a temperature range of -20°C to 60°C, and a positive electrode active material areal loading greater than or equal to 5 mg / cm². -2 Under certain conditions, the quasi-solid-state sodium metal battery can undergo stable charge-discharge cycles.